Racial equity on college campuses : connecting research and practice - Johnson, Royel M.; Anya, Uju; Garces, Liliana M. (SUNY series, critical race studies in education., 2022)
"Offers insight into race-based disparities in higher education and practical tools for advancing racial equity on college and university campuses"--